2012
DOI: 10.1007/s11434-011-4955-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipids of sulfate-reducing bacteria and sulfur-oxidizing bacteria found in the Dongsheng uranium deposit

Abstract: U-bearing sandstones from the Dongsheng deposit in Ordos Basin contain abundant C 15 -C 18 fatty acids. The fatty acids may have been derived from modern and ancient organisms including organisms from the intervals of U mineralization. A certain amount of i15:0, a15:0, a17:0 fatty acids coexist with small amounts of i17:1ω7c and 10me16:0, characteristic biomarkers of Desulfovibrio and Desulfobacter sp., respectively. This indicates the existence of sulfate-reducing bacteria (SRB) in the sandstones. The presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This model is mainly based on mineralogical biosignatures: Microorganism-like structures identified in the ores are composed of 5-to 20-nm coffinite nanoparticles and contain biologically important elements, such as P and K. Furthermore, the intimate intergrowth of coffinite with 34 S-depleted ore-stage pyrite and calcite with negative d 13 C values also supports a biogenic origin. The biogenic model was further confirmed by Jiang et al (2012), who found lipids of sulfate-reducing and sulfur-oxidizing bacteria in the deposit. The ores were emplaced via reduction in the ore species derived from oxygenated, slightly alkaline groundwater flowing through the host rocks.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…This model is mainly based on mineralogical biosignatures: Microorganism-like structures identified in the ores are composed of 5-to 20-nm coffinite nanoparticles and contain biologically important elements, such as P and K. Furthermore, the intimate intergrowth of coffinite with 34 S-depleted ore-stage pyrite and calcite with negative d 13 C values also supports a biogenic origin. The biogenic model was further confirmed by Jiang et al (2012), who found lipids of sulfate-reducing and sulfur-oxidizing bacteria in the deposit. The ores were emplaced via reduction in the ore species derived from oxygenated, slightly alkaline groundwater flowing through the host rocks.…”
Section: Introductionmentioning
confidence: 65%
“…The biogenic model was further confirmed by Jiang et al . (), who found lipids of sulfate‐reducing and sulfur‐oxidizing bacteria in the deposit. The ores were emplaced via reduction in the ore species derived from oxygenated, slightly alkaline groundwater flowing through the host rocks.…”
Section: Introductionmentioning
confidence: 99%
“…(Fossing et al, 1995; Schulz et al, 1996; Jørgensen and Gallardo, 1999) resemble Trichichnus in the 3-D scanner images. Moreover, the common pyritization of Trichichnus is related to sulfate-reducing bacteria, like δ -proteobacteria Desulfovibrio spp., which can co-occur with sulfur-oxidizing bacteria, such as Beggiatoa or Thioploca (e.g., Jiang et al, 2012). Therefore, we consider Thioploca -like, mat-forming, large sulfur bacteria and related filamentous sulfide-oxidizing bacteria (see Teske et al, 1995) as a trace maker of Trichichnus tunnels and their spatial organization.…”
Section: Discussionmentioning
confidence: 99%
“…(Fossing et al, 1995;Schulz et al, 1996;Jørgensen and Gallardo, 1999) resemble Trichichnus in the 3-D scanner images. Moreover, the common pyritization of Trichichnus is related to sulfate-reducing bacteria, like δ-proteobacteria Desulfovibrio spp., which can co-occur with sulfur-oxidizing bacteria, such as Beggiatoa or Thioploca (e.g., Jiang et al, 2012). Therefore, we consider Thioploca-like, matforming, large sulfur bacteria and related filamentous sulfide-oxidizing bacteria (see Teske et al, 1995) as a trace maker of Trichichnus tunnels and their spatial organization.…”
Section: Discussionmentioning
confidence: 99%